Peningkatan Pemahaman Pembelajaran IPA Materi Perkembangbiakan Bunga Sutra Bombay Melalui Metode Outdoor Learning Bagi Disabilitas Rungu - Ruwaidah, Ruwaidah; Budi, Setia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to improve the understanding of science learning on the propagation of bombay silk flowers through the outdoor learning method for students with hearing disabilities. This research method is Classroom Action Research (PTK). The data collection techniques used are tests, observations, and documentation. The data produced were analyzed qualitatively and quantitatively. The results show that the outdoor learning method improves students' understanding. Based on the test, AG obtained a score of 92.3% while MA and KL 84.6%, Based on the results of the research that has been carried out and presented in chapter IV, it can be concluded that the understanding of science of bombay silk flower breeding material for Class IX deaf people at SLB N 1 Lubuk Basung can be improved through the outdoor learning method.